Trends of colorectal cancer incidence according to age, anatomic site, and histological subgroup in Bavaria: A registry-based study - Voigtländer, Sven; Hakimhashemi, Amir; Grundmann, Nina; Rees, Franziska; Meyer, Martin; Algül, Hana; Müller-Nordhorn, Jacqueline (Frontiers in Oncology, 2022)
Background Recent studies reported an increase in colorectal cancer incidence for adults below 50 years. There is a lack of studies distinguishing between histological subgroups, especially from Europe. Methods Using data from the Bavarian Cancer Registry, we analyzed incidence trends in colorectal cancer by age (20–29, 30–39, 40–49, and 50 years and above), anatomic site (colon without appendix, appendix, and rectum), and histological subgroup (adenocarcinoma and neuroendocrine neoplasm) from 2005 to 2019. We calculated 3-year average annual age-standardized incidence rates (ASIR) per 100,000 persons for the beginning (2005–2007) and the end (2017–2019) of the study period and estimated average annual percentage change. Results Data from 137,469 persons diagnosed with colorectal cancer were included. From 139,420 cases in total, 109,825 (78.8%) were adenocarcinomas (ACs), 2,800 (2.0%) were neuroendocrine neoplasms (NENs), and 26,795 (19.2%) had other histologies. This analysis showed a significant increase in the 3-year average annual ASIR of colorectal NENs in all age groups between 2005–2007 and 2017–2019 with the highest increase in the age groups 30–39 years (0.47 to 1.53 cases per 100,000 persons; +226%; p < 0.05) and 20–29 years (0.52 to 1.38 cases per 100,000 persons; +165%; p < 0.05). The increase was driven by appendiceal and rectal NENs but not by colonic NENs. The 3-year average annual ASIR of colorectal ACs did not change significantly for the age groups below 50 years. For those aged 50 years and above, the 3-year average annual ASIR of colorectal ACs decreased significantly (132.55 to 105.95 cases per 100,000 persons; −20%; p < 0.05]). The proportion of NENs increased across all age groups, especially in the younger age groups. Conclusion Future studies that analyze trends in early-onset colorectal cancer need to distinguish between anatomic sites as well as histological subgroups and may, thus, provide useful information regarding the organization of colorectal cancer screening, which primarily helps to detect adenomas and adenocarcinomas."